Spatiotemporal three-dimensional transport dynamics of endocytic cargos and their physical regulations in cells - Chao Jiang (iScience, 2022)
Summary: Intracellular transport, regulated by complex cytoarchitectures and active driving forces, is crucial for biomolecule translocations and relates to many cellular functions. Despite extensive knowledge obtained from two-dimensional (2D) experiments, the real three-dimensional (3D) spatiotemporal characteristics of intracellular transport is still unclear. With 3D single-particle tracking, we comprehensively studied the transport dynamics of endocytic cargos. With varying timescale, the intracellular transport changes from thermal-dominated 3D-constrained motion to active-dominated quasi-2D motion. Spatially, the lateral motion is heterogeneous with peripheral regions being faster than perinuclear regions, while the axial motion is homogeneous across the cells. We further confirmed that such anisotropy and heterogeneity of vesicle transport result from actively directed motion on microtubules. Strikingly, inside the vesicles, we observed endocytic nanoparticles make diffusive motions on their inner membranes when microtubules are absent, suggesting endocytic cargos are normally localized at the inner vesicle membranes through a physical connection to the microtubules outside during transport.